THE EFFICACY OF NURSE-LED CLINICAL ADVANCEMENT INITIATIVES AND PROGRAMS FOR CAREER PROGRESSION - Sarah Mubarak Bajuwaiber, Sahar Abdullah Alqarni, Khulood Eissa Aswani, Abdulsalam Saud Said Alshallali, Essa Salah Aljohani, Emad Faisal Shabander, Naif Noman Alshammari, Seham Abdallah Al-Harbi, Ohud Salem G Alshammari,; Hanan Maran J Alanazi, Shaaa Thani Alshammari, Mashael Thani Alshammari, Hanan Hamoud A Aldhafeeri, Abdullah Mohammed Albakri (Chelonian Research Foundation, 2022)
Advanced nurse practitioners play a crucial role in enhancing the quality of patient care and have significant potential to enhance the overall health of individuals worldwide. Following the official acknowledgment of advanced nurse practitioners by the International Council of Nurses and other relevant organizations, this function has been widely implemented in many departments and clinical specializations, especially in nations with high economic levels. To assess the efficacy of advanced nurse practitioners in comparison to physicians-led/usual care (care overseen by medical doctors or non-advanced nurse practitioners). The databases MEDLINE, EMBASE, CINAHL, Cochrane registry, Cochrane trials, and Cochrane EPOC (PDQ Evidence) were searched that examined the effects of advanced nurse practitioners on patient care and health resource utilization outcomes. The findings of this review provide evidence supporting the positive impact of advanced nurse practitioners on various clinical and service-related outcomes. These outcomes include patient satisfaction, waiting times, management of chronic diseases, and cost-effectiveness. The positive effects were particularly notable when comparing advanced nurse practitioner-led care to care provided by medical practitioners or usual care practices. The review encompassed primary, secondary, and specialist care settings, and included both adult and pediatric populations. Keywords: Advanced Nurse Practitioners (ANPs) Initiatives, Programs, Career Progression.